Characteristics of beef nuggets affected by adding soya meat - Mumu, MM; MS Islam; Islam, SS (Meat Research, 2022)
The study was conducted to characterize nutritional, sensory quality and economic feasibility of beef nuggets as affected by adding soya meat. Therefore, the experiment was conducted with a view to investigate inclusion of soya meat in beef nuggets with five (5) treatments (T0 = 100% beef; T1 = 75% beef + 25% soya meat; T2 = 50% beef + 50% soya meat; T3 = 25% beef + 75% soya meat and T4 = 100% soya meat) having three (3) replications. The results indicated that the incorporation of soya meat decreased moisture, crude protein, ether extract and cooking loss but increased amount of carbohydrate, ash and cooking yield in beef nugget. Highly significant (<0.001) differences were observed in moisture, crude protein, ether extract, ash, carbohydrate and cooking yield. L* values increased and a* values decreased with high level of soya meat incorporation. No significant difference was observed in color parameter except in L* values. Incorporation of soya meat decreased aroma and taste score of beef nugget whereas appearance and texture indicated the highest score. Production cost was reduced for incorporating soya meat in beef nugget. Beef nugget treated with 25% to 75% soya meat inclusion found to be more acceptable in terms of sensory evaluation and economic feasibility.